2022
DOI: 10.1111/ans.17566
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 on appendicitis presentations in children in Australia and New Zealand

Abstract: Background: In contrast to many countries, the prevalence of COVID-19 in Australia and New Zealand has been low. We hypothesised, however, that a potential secondary effect of the COVID-19 pandemic would be delayed presentation of paediatric appendicitis, with resultant higher rates of complicated appendicitis. This study was an initiative of the Australian and New Zealand Surgery in Children Registrars' Association for Trials collaborative, a trainee-led research group based in Australia and New Zealand. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(40 reference statements)
0
2
0
Order By: Relevance
“… 20 found no delay in presentation and no significant difference in the rates of complicated appendicitis. Another retrospective study conducted in Australia and New Zealand also concluded no difference in the presentation of symptoms and complication rates, with no delay in presentation to the emergency department 21 .…”
Section: Prevalence and Epidemiology Of Acute Appendicitis In Vulnera...mentioning
confidence: 94%
See 1 more Smart Citation
“… 20 found no delay in presentation and no significant difference in the rates of complicated appendicitis. Another retrospective study conducted in Australia and New Zealand also concluded no difference in the presentation of symptoms and complication rates, with no delay in presentation to the emergency department 21 .…”
Section: Prevalence and Epidemiology Of Acute Appendicitis In Vulnera...mentioning
confidence: 94%
“… 36 also reported that 8 out of 10 patients underwent appendectomy. A retrospective study in Australia and New Zealand showed that the management of pediatric acute appendicitis remained the same during the pandemic, when almost all patients underwent laparoscopic appendicectomy 21 .…”
Section: Changes To the Management Of Pediatric Appendicitis During T...mentioning
confidence: 99%
“…A comunidade foi alertada de várias formas sobre a prevenção de contatos e os serviços públicos e as atividades escolares foram restringidas. Houve diversos relatos em vários países de quadros de AA mais complicados tendo em vista o retardo para o acesso ao diagnóstico e ao tratamento da apendicite aguda [1][2][3][4][5][6][7][8][9][10][11] .…”
Section: Introductionunclassified